A Review of Metadiscourse Research - Liu, Yanfei; Ernisa, Marzuki; Joseph, Ramanair; Zhao, Baoying (Transnational Press London Ltd, 2025)
The concept of metadiscourses has developed greatly since it was proposed by Zelig Harris in 1959. This study provides a comprehensive overview of the definitions of metadiscourse and evolution of metadiscourse studies. In addition, the research patterns of metadiscourse research in major academic databases are analyzed. We find that metadiscourse research is keeping an upward tendency since the occurrence of this term and has boomed in recent years, especially in academic writing, whether from synchronic or diachronic perspective. Synchronic studies examine metadiscourse in a variety of written and oral contexts, revealing interdisciplinary and cross-cultural differences; while diachronic studies trace the historical development of metasdiscourse practices. The paper demonstrates the growing research interest in metadiscourse and offers future prospects for scholars.